Horizontal ecological compensation zoning and standard in China’s major grain-producing areas based on virtual cultivated land flow - Jing Chen; Jing Chen; Shan Yang; Shan Yang; Hui Du; Hui Du; Weizhan Liang; Yunliang Liu (Frontiers in Environmental Science)
IntroductionChina’s main grain-producing areas (MGPA) have made outstanding contributions to cultivated land protection and food security. Integrating cultivated land use with socio-economic activities and constructing a horizontal ecological compensation mechanism under the virtual cultivated land (VCL) framework are important measures for achieving the “Trinity Comprehensive Protection” of quantity, quality, and ecology cultivated land.MethodsWe used the North China Plain (NCP) as the research area and the multiregional input–output model to analyze inter-regional VCL flow, and ecological compensation standard was calculated based on the ecosystem services value. Results(1) VCL flowed from economically underdeveloped regions (e.g., Hebei, Shandong, and Henan) to economically developed regions (e.g., Beijing and Tianjin). As a net outflow region, the NCP provided VCL for the Yangtze River and Pearl River deltas (2) The compensation standards ranged from 2192–18406 yuan/hectare. Net inflow regions were payment areas, and net outflow regions were receiving areas. Beijing and Tianjin should pay 3.04 and 0.70 billion yuan for other provinces. The NCP should obtain 17.35 billion yuan from other regions in China.DiscussionThe research framework provides a basis for division of responsibility for cultivated land protection and offers ideas and frameworks for horizontal ecological compensation of cultivated land.